Stroke outcomes in patients undergoing percutaneous coronary intervention in clinical practice today. (June 2011) - Werner, Nicolas; Zeymer, Uwe
Cardiac catheterization and percutaneous coronary intervention (PCI) are considered to be safe procedures with low complication rates. Nevertheless, periprocedural stroke affects thousands of patients undergoing PCI worldwide every year especially in a continually aging population carrying a higher risk for complications in general. Stroke after PCI is a rare, but still a notable complication carrying an enormous impact on the patient''s prognosis and on quality of life. Large registries reflecting a ''real-world'' situation reported an occurrence of stroke in 0.18––0.44% of an unselected population undergoing PCI in clinical routine today. An advanced age, PCI under emergency conditions, history of stroke, renal failure, the use of intra-aortic balloon pump, congestive heart failure, interventions during bypass grafts and vascular risk factors such as arterial hypertension and diabetes mellitus have been reported to be risk factors for stroke complicating PCI. Several analyses have shown that stroke is associated with high mortality rates ranging from 22 to 37% in large registries. If patients survive this devastating complication, most suffer from persistent neurological deficits such as motor or speech disorders. Owing to its low incidence, no randomized trials exist on this topic, which has so far precluded the development of an evidence-based treatment. Intra-arterial thrombolysis seems to be a promising and relatively safe approach in the treatment of periprocedural ischemic stroke, but further research is needed to validate its efficacy and safety in the special setting of PCI.